Quality of life of Lithuanian women with early stage breast cancer - Ostapenko Valerijus; Veseliunas Jonas; Bulotiene Giedre (BMC, 2007)
Abstract Background In the last decades, there have been no studies carried out in Lithuania on the quality of life of breast cancer patients. The aim of the present study was to evaluate changes in the quality of life of Lithuanian women with the early stage of breast cancer nine months after surgery and its dependence on surgical strategy, adjuvant chemotherapy and the social and demographic status of the patients. Methods Seventy-seven patients with early stage breast cancer filled in the FACT-An questionnaire twice: one week and nine months after the surgery. The main age of the patients was 53.1 ± 10.6 years. We distinguished the mastectomy group and breast conserving treatment (BCT) group with/without chemotherapy. The groups were identical in their social and demographic status (age, education, occupation and marital status). Changes in the quality of life in these groups were compared nine months after surgery. Results Nine months after surgery, the overall quality of life was found worse in both mastectomy and BCT groups. Changes were induced by the worsening of the emotional and social well-being. The quality of life became worse in the mastectomy plus chemotherapy sample. No changes were detected in the mastectomy group without chemotherapy. In addition, the multivariate analysis showed that the marital status was quite a significant determinant of the functional well-being. Conclusion Nine months after surgery, the study revealed a worsening of the overall quality of life in both groups of patients - those who had undergone mastectomy and BCT. The quality of life became considerably worse in the mastectomy plus chemotherapy group. Marital status was found to exert the most considerable influence on the women's quality of life in comparison with other social and demographic factors.